Processing and thermal analysis of palm oil and dye filled polypropylene / Nusoibah Naahidhah Rukman - Rukman, Nusoibah Naahidhah (2008)
The determinations of Polypropylene (PP) with additive namely palm oil and curcumin was investigated. Palm oil composed of fatty acids which were esterified with glycerol. Palm oil can act as lubricant and can enhance the flow rate of the polymer compounds. Curcumin can be used to bind with polymers and can act as antioxidant and reduce the toxicity of the polymers. The used of antioxidants in polymer processing can offer better stabilization of the polymer during processing and also prolong its useful life in the end application. The mixing process was done using twin screw extruder with melt temperature between 180°C to 205°C and screw speed of 258 rpm. The torque value was lONm. After mixing process, the extrudates were palletized and the pallet samples were tested for their thermal analysis by using Thermal Gravimetry Analysis (TGA), Differential Scanning Calorimetry (DSC), and Hot Stage Micron Microscope. TGA was used to determine